AN ATTEMPT AT DEFINING AND ORDERING MEANINGS RELATED TO GEOPOETICS - Weretiuk, Oksana (Porównania, 2012)
The meanings of geopoetry were considered in its relation with: ecology and ecocriticism, geopolitics, regional literature, urbanism, space semantic studies, globetrotterism, with the help of exemplification of the selected fragments from Ukrainian, Russian, Polish and Canadian literature, as well as references to American literature. Six basic meanings of geopoetry were distinguished: (1) the original White’s geopoetics as study of Man-Earth relation; (2) the international intellectual and artistic literary movement (France, Scotland, Belgium, Germany, Switzerland, Italy, Canada, Russia, Ukrainian Crimea, Serbia), which was initiated by Kenneth White in France in 1989; (3) a certain way of perception of the world and artistic creation (artistic technique, designed for the poetry of the earth and understanding of one’s land); (4) works of literary art which were created with the help of such technique (geopoetry, which is not at all times identical with geographical/geological poetry – wider – with literary works created by geologists, geophysicists, etc. who disclose their professional subject – the earth (geo) on the thematic level of their literary works). (3) and (4), taken together, perform also the implementation of White’s ideas; (5) geocriticism, a method of literary analysis and interpretation (in Bertrand Westphal’s and Robert T. Tally’s meaning, which is the creative continuation of White’s conception); (6) teaching activity.